Assessing the impact of a vi-polysaccharide conjugate vaccine in preventing typhoid infections among Nepalese children: a protocol for a phase III, randomized control trial - Theiss-Nyland, K; Shakya, M; Colin-Jones, R; Voysey, M; Smith, N; Karkey, A; Dongol, S; Pant, D; Farooq, Y; Neuzil, K; Shrestha, S; Basnyat, B; et al. (Oxford University Press, 2019)
Background Enteric fever is estimated to affect 11–20 million people worldwide each year. Morbidity and mortality from enteric fever primarily occur in lower-income countries, with children under 5 years of age experiencing a significant portion of the burden. Over the last few decades, the control of enteric fever has focused primarily on improved water and sanitation, with the available vaccines unsuitable for children and primarily used by travelers. A new typhoid conjugate vaccine (Vi-TCV), prequalified by the World Health Organization (WHO) and highly immunogenic in children under 5, has the potential to reduce the typhoid burden in endemic countries. Methods This study is a double-blinded, randomized, controlled trial with a 2-year follow-up to assess the protective impact of the Vi-TCV vaccine, compared with a control vaccine, in children from 9 months to 16 years of age. The primary outcome of interest is the reduction in the number of culture-confirmed typhoid cases attributable to Vi-TCV. Approximately 20 000 children living in the Lalitpur district, within the Kathmandu valley, will be enrolled in the study and followed to measure both safety and efficacy data, which will include adverse events, hospitalizations, antibiotic use, and fever frequency. Results Both the intervention and control vaccines are WHO prequalified vaccines, which provide a health benefit to all participants. Children have been chosen to participate because they bear a substantial burden of both typhoid morbidity and mortality in this population. The results of this study will be disseminated through a series of published articles. The findings will also be made available to the participants and the broader community, as well as local stakeholders, within Nepal. Conclusions This is the first large-scale, individually randomized, controlled trial of Vi-TCV in children in an endemic setting, and will provide new data on Vi-TCV field efficacy. With Vi-TCV introduction being considered in high-burden countries, this study will support important policy decisions. Clinical Trials Registration The trial is registered on the ISRCTN registry (for details, see https://doi.org/10.1186/ISRCTN43385161; registry number: ISRCTN 43385161).